2006
DOI: 10.1063/1.2422906
|View full text |Cite
|
Sign up to set email alerts
|

Off-resonance surface plasmon enhanced spontaneous emission from CdTe quantum dots

Abstract: Surface plasmon ͑SP͒ enhanced photoluminescence ͑PL͒ from CdTe quantum dots ͑QDs͒ on monolayers of Au nanoparticles is investigated under both resonant and nonresonant conditions. Enhancement of the QD PL intensity is observed when the emission spectrum is redshifted with respect to the SP absorption resonance. Coupling to the SPs results in a redshift and broadening of the PL spectrum, and an increase in the PL decay rate. The largest coupling is observed for QD monolayers with peak emission at 667 nm, produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
93
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 22 publications
(23 reference statements)
7
93
3
1
Order By: Relevance
“…5,6 The near-field of the plasmonic structure can modify the emission of a fluorophore. [7][8][9][10][11][12] Depending on the plasmonic properties of the metallic nanoparticle (MNP) it can lead to quenching or enhancement of the fluorophore emission. The modified emission can be a consequence of many processes such as NRET to the MNP, scattering and absorption by the MNP, and changes in the emitter's radiative and nonradiative decay rates.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 The near-field of the plasmonic structure can modify the emission of a fluorophore. [7][8][9][10][11][12] Depending on the plasmonic properties of the metallic nanoparticle (MNP) it can lead to quenching or enhancement of the fluorophore emission. The modified emission can be a consequence of many processes such as NRET to the MNP, scattering and absorption by the MNP, and changes in the emitter's radiative and nonradiative decay rates.…”
Section: Introductionmentioning
confidence: 99%
“…The distance dependent acceptor QDs' PL lifetime intensities are also shown in the figure as an inset. The dotted line is a reference one, which is the acceptor QDs' intensity from the mixed dots, when they are on the 6 When the layer of mixed QDs is in very close to the Au NPs, i.e., up to eight PE bilayers, the acceptor QDs' intensities are quenched due to the nonradiative energy transfer from the QDs to the Au NPs. Here, we note that the pure monolayer of acceptor QDs' PL lifetime intensities with the Au NPs is not shown the distance dependence.…”
mentioning
confidence: 99%
“…3 Efforts to improve the FRET process have been focused on structures with reduced donor-acceptor QDs' separation, improved spectral overlap of the donor emission and acceptor absorption spectra, and increased packing density of the layers. 4 Metal nanoparticles ͑NPs͒ have been used to modify some of the fundamental optical processes such as Raman scattering 5 and radiative processes 6 in chemical species in a characteristic way. In this letter, we present the experimental evidence for the enhanced FRET between the CdTe QDs at nanoscale proximity to Au NPs, motivated by the previous theoretical studies, which indicated the potential to accelerate the FRET process between the donor and acceptor molecules 7 and QDs ͑Ref.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1-3 More recently, the coupling of a QD to the plasmon resonance of a metal nanoparticle or nanoparticle array has attracted much attention, representing the ultimate electromagnetic resonator with subwavelength size. Such hybrid QD-metal nanoparticle structures enable the enhancement of the QD emission, [4][5][6][7] control of the polarization of emitted light, 8 modification of the far field radiation pattern, 9 and other interesting collective optical phenomena. 10,11 So far, fabricating those structures relied on chemical self-assembly 12 or top-down processing, 8 the latter being without control of the position of the QDs with respect to the metal nanostructures which is required to fully exploit their unique properties.…”
mentioning
confidence: 99%